Influence of coalification on pore structure evolution in middle-ranked coals - Zhou, Xuejiao; Hou, Haihai; Li, Heng (Frontiers in Earth Science, 2023)
The influence of coalification on coal structure evolution in middle ranked coals is significant for physical assessment of coalbed methane (CBM) reservoirs, which provides insights on the intrinsic connection between coalification jump and pore heterogeneity. A total of 26 middle-ranked coals were samples covering Liupanshui Coalfield in Guizhou Province, Anhe Coalfield in Henan Province, Huaibei Coalfield in Anhui Province, Sanjiang Basin in Heilongjiang Province, Ordos Basin in Shaanxi Province and Qinshui Basin in Shanxi Province. Based on a series of experiments including vitrinite reflectance, coal maceral identification, nitrogen adsorption and the pore fractal method, the inner link between physical property parameters of coal reservoirs and coal rank was revealed. The results show that the coal maceral in middle rank coals is dominated by vitrinite and inertinite and two types of adsorption pores are divided according to the nitrogen adsorption/desorption curves along with pore size distribution. The specific surface area is positively correlated with total pore volume, micropore volume and negatively correlated with averaged pore size and transitional pore volume. The coal samples with low average pore sizes have relatively high total pore volume, specific surface area and micropore volume per unit nm. With the increase of coal rank, the fluctuating points of micropore and transitional pore volume correspond to 1.16-1.19%, 1.41-1.43% and 1.86-1.91% of Ro, max, respectively. The boundary of Ro, max corresponding to the second coalification jump can be more specifically defined as 1.16-1.19% from the established nominal range of 1.1-1.3%. The pore fractal dimension DNA1 and DNA2 increase with increasing specific surface area. Furthermore, the DNA2 has a negative correlation with micropore volume and averaged pore size, indicating that the coal with smaller average pore diameter and lower micropore content has a more complex pore structure.